Approaching measles elimination in Switzerland: changing epidemiology 2007–2018 (Swiss Medical Weekly, 2019)
Switzerland is aiming to eliminate measles, in line with the objectives of the World Health Organization (WHO). Physicians, laboratories and public health authorities have made great efforts to reach this goal. A continually increasing measles vaccination coverage and other preventive measures have made an impact: no major measles outbreak has been recorded since 2011. In order to evaluate progress towards elimination, measles epidemiology of a previous epidemic period (2007–2011) was compared with the current post-epidemic period (2012–July 2018) by analysis of data from the mandatory notification system. A decrease of 94% in the average annual incidence rate occurred between the two periods (from 133 to 9 cases per million inhabitants). This was accompanied by significant changes in the epidemiology that are expected and characteristic of countries with limited circulation of the measles virus. After analysing the performance of the Swiss surveillance system and the data provided, the WHO concluded that endemic measles transmission was interrupted in Switzerland in 2016 and 2017.